Analysis of electromagnetic signature of Arabic alphabet as RF elementary coding particles. Issue 2 (16th December 2015) - Boularess, Oussama; Rmili, Hatem; Aguili, Taoufik; Tedjini, Smail
Abstract : This paper discusses the electromagnetic (EM) signature of Arabic alphabets that can be considered as standards particles to form chipless tags. Normalized Arial font is suited as example but the method can be applied for any other font. The letters are realized by metallic strips or better, by conductive ink. All the 28 letters have been simulated and their EM signatures for both field polarizations are extracted. It is demonstrated that combining vertical and horizontal responses allow the identification of letters without ambiguity. Moreover, the case of letter with punctuation (one to three points) is considered in more details. Indeed, we propose to modify very slightly these letters by connecting the points to the body of the letters. This connection is made by a unique straight and very thin strip. Under this modification these letters exhibit more exploitable signatures. Finally, a lookup table for identification of the 28 letters is carried out.